The Effects of Prior Restraint and Noncontingent Preshock on Acquisition of an Escape Response in the Rat - Bracewell, John Robert (My University, 1972)
The three experiments reported in this thesis investigated the effects of restraint and of randomly presented, fixed duration preshocks on subsequent shuttlebox escape-from-shock learning. Fixed-intensity preshock, random-intensity preshock, and no-preshock conditions were included in each experiment. In Experiment 1, restraining the rat in a harness both during preshock and during nopreshock conditions prior to escape training retarded escape acquisition. There was no effect of preshock. In Experiment 2, independent retarding effects of restraint and high fixedintensity (1.0 ma) preshock were found, whether escape training occurred immediately or 24 hours after preshock. In Experiment 3, a condition in which movement was punished by positively correlating preshock intensity with the rat's movement retarded escape conditioning. No effects were found for fixed-intensity or random-intensity preshock, nor for a condition in which movement was rewarded during preshock. The retarding effects of restraint and certain types of preshock were explained in terms of interfering instrumental responses.
Keywords: Psychology; Psychology